KARAKTERISTIK VERBA DAN ADJEKTIVA DALAM IKLAN APLIKASI PINJAMAN ONLINE - Putra, Dona Aji Karunia (Sunan Kalijaga State Islamic University Yogyakarta, 2022)
Advertisements tend to be packed with strong, persuasive, and emotional language. To be able to create a persuasive and emotional effect, proper linguistic features are needed. This study aims to reveal linguistic features in the form of verbs and adjectives as the main weapon in online loan advertising. In addition, this study also seeks to see the relationship between the use of adjectives in online loan advertisements with the public's view. The research method used is descriptive qualitative. The data in this study are in the form of verbs and adjectives contained in online loan application advertisements. The data sources in this study are online loan advertisements registered with the OJK. The results show that the use of verbs in online loan advertisements tends to achieve interrogative and imperative functions. The use of “cepat”, “aman”, and “mudah” adjectives is intended as a strategy to increase the selling value and attractiveness of loan products. The use of “cepat”, “aman”, and “mudah” adjectives in online loan advertisements tends to describe changes in people's views or mindsets in general, especially in the economic field (loan services).